Transformation of the Peregrine Breather Into Gray Solitons on a Vertically Sheared Current - Hsu, H. C.; Abid, M.; Chen, Y. Y.; Kharif, C. (Frontiers in Physics, 2021)
In this Brief Research Report, we have shown, within the framework of the vor-NLS equation in deep water, that the Peregrine breather travelling at the free surface of a shear current of slowly varying vorticity may transform into grey solitons.